2020
DOI: 10.1109/access.2020.3010849
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Decisions Analysis in an Online Shopping Service Supply Chain Considering Reciprocal Altruism

Abstract: Cooperative relationships and interactive decision behaviors between online stores and thirdparty logistics (TPL) have attracted increasing attention from academics as well as practitioners with the development of the online retailing industry. However, the decisions and performance of each member in a decentralized supply chain are not in line with the actual performance and decision behaviors of them, especially when taking individual altruism preference into account. Hence, without considering the truism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
(56 reference statements)
0
1
0
1
Order By: Relevance
“…Um alto nível de serviço logístico pode atrair novos clientes e manter os antigos nos canais online, de acordo com Qin et al (2020). Portanto, a conversão de novos pedidos estudada nesta pesquisa baseia-se nesse preceito.…”
Section: Contribuição Da Literaturaunclassified
“…Um alto nível de serviço logístico pode atrair novos clientes e manter os antigos nos canais online, de acordo com Qin et al (2020). Portanto, a conversão de novos pedidos estudada nesta pesquisa baseia-se nesse preceito.…”
Section: Contribuição Da Literaturaunclassified
“…Liu et al [46] examined a logistics service supply chain and showed that both the altruism of the logistics service integrator and that of a functional logistics service provider could enhance the supply chain profit. Qin et al [47] took a bilateral evolutionary approach to investigate an online shopping service supply chain and illustrated that the bilateral altruism decreases the retail price and service price while increasing the service level. Ma et al [48] analyzed a product-service supply chain in the online-to-offline environment, and found that bilateral altruism between the manufacturer and the retailer is useful for developing higher quality products, better service, and greater goodwill.…”
Section: Altruism In Agricultural Supply Chainmentioning
confidence: 99%